Outcomes for individuals turned down for living kidney donation. Issue 12 (28th October 2018) - Reese, Peter P.; Allen, Matthew B.; Carney, Caroline; Leidy, Daniel; Levsky, Simona; Pendse, Ruchita; Mussell, Adam S.; Bermudez, Francisca; Keddem, Shimrit; Thiessen, Carrie; Rodrigue, James R.; Emanuel, Ezekiel J.
Abstract: Background: A better understanding of the consequences of being turned down for living kidney donation could help transplant professionals to counsel individuals considering donation. Methods: In this exploratory study, we used survey instruments and qualitative interviews to characterize nonmedical outcomes among individuals turned down for living kidney donation between July 1, 2010 and December 31, 2013. We assembled a comparator group of kidney donors. Results: Among 83 turned‐down donors with contact information at a single center, 43 (52%) participated in the study (median age 53 years; 53% female; 19% black). Quality of life, depression, financial stress, and provider empathy scores were similar between individuals turned down for donation (n = 43) and donors (n = 128). Participants selected a discrete choice response to a statement about the overall quality of their lives; 32% of turned‐down donors versus 7% of donors ( P  < 0.01) assessed that their lives were worse after the center's decision about whether they could donate a kidney. Among turned‐down donors who reported that life had worsened, 77% had an intended recipient who was never transplanted, versus 36% among individuals who assessed life as the same or better ( P  = 0.02). In interviews, the majority of turned‐down donors reported emotional impact, including empathy, stress, and other challenges, related to having someone in their lives with end‐stage kidney disease. Conclusions: Generic instruments measuring quality of life, depression, financial stress, and provider empathy revealed no significant differences between kidney donors and turned‐down donors. However, qualitative interviews revealed preliminary evidence that some turned‐down donors experienced emotional consequences. These findings warrant confirmation in larger studies.